2021
DOI: 10.3390/pr9020299
|View full text |Cite
|
Sign up to set email alerts
|

Rhizopus oligosporus-Assisted Valorization of Coconut Endosperm Waste by Black Soldier Fly Larvae for Simultaneous Protein and Lipid to Biodiesel Production

Abstract: Coconut endosperm waste (CEW) was treated by Rhizopus oligosporus via in situ and ex situ fermentations together with bioconversion into valuable black soldier fly larval biomass. The ex situ fermentation could overall enrich the nutritional compositions of CEW by hydrolyzing its complex organic polymers and exuding assimilable nutrients to enhance the black soldier fly larvae (BSFL) growth. Nevertheless, the larval gut bacteria were competing with Rhizopus oligosporus in in situ fermentation, derailing the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The content of protein and fat in larvae have not been analyzed in this study. However, previous studies on bioconversion of fermented CEW have reported the following values: protein 15-39% [18,20,22] and fat 44-58% [18,21,22]. Analysis of protein and fat in larvae reared on PPBS is recommended for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of protein and fat in larvae have not been analyzed in this study. However, previous studies on bioconversion of fermented CEW have reported the following values: protein 15-39% [18,20,22] and fat 44-58% [18,21,22]. Analysis of protein and fat in larvae reared on PPBS is recommended for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bioconversion of the liquid is therefore substantially higher than for the sediment, which illustrates the need for further research on improved fermentation of PPBS. Important fermentation factors not tested in this study are water content [9,[18][19][20][21], process duration [9,19,20], and co-fermentation [33] as well as inoculum concentration [19][20][21][22]. Several methods to improve fermentation of lignocellulose by pre-processing have been reported: physical using microwaves, ultrasound, steam explosion, or heating; biological using microorganisms or fungi (i.e., white root fungi); and chemical using strong acids, alkalis, organic solvents, or ionic liquids [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8]. Improving nutrient availability by anaerobic digestion is one method of pretreatment that has been discussed recently [8][9][10][11][12][13][14][15][16]. Disintegration, hydrolysis, acidogenesis (also called fermentation), acetogenesis, and methanogenesis are the steps in anaerobic digestion [17]: large organic compounds are first broken down into monomers, then further converted by microorganisms to volatile fatty acids (VFAs), alcohols, carbon dioxide, hydrogen, and methane [18].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the larval transamination pathway, the microbial biomass pathway could reduce manure NH 3 emissions if NH 3 -N assimilation in larvae is maximized via rearing conditions. For instance, substrates inoculated with microbes can increase both bioconversion and larval weights (Mazza et al, 2020;Wong et al, 2021), although this is not always the case (Gold et al, 2021;Hasnol et al, 2020). Future assessments should elucidate if increased bioconversion due to specific microbial inocula is correlated with larger NH 3 -N assimilation in manurebased diets.…”
Section: Opportunities and Outlookmentioning
confidence: 99%